ҚАРАҚАЛПАҚ ҲӘМ ҚАЗАҚ ЖЫРЛАРЫНДАҒЫ ОБРАЗЛАРДЫҢ УҚСАСЛЫҒЫ ХӘМ АЙЫРМАШЫЛЫҚЛАРЫ - Базарбаева, Г. (ILIM hám JÁMIYET, 2022)
The article deals with the comparative study of Karakalpak epics and Kazakh poems. The object of research is the epic "Er Shora" of the Karakalpak nation and the epic "Shora" of the Kazakh nation. The destinies of the heroes are very similar in these epics, their survival, intelligence, respect for their parents, nation, and loyalty to their lovers, and some peculiarities of the characters are analyzed through examples.